Analisis Kelayakan Finansial pada Proyeksi Bisnis Sentra Mebel di Kabupaten XYZ - Khasanah, Annisa Uswatun; Wicaksono, Z Arifin; Suryani, Dewi Amanatun; Permanawati, Zaenab Fitria (Universitas Islam Indonesia, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play a crucial role in supporting Indonesia’s economy, including the furniture sector, which holds significant development potential. XYZ Regency is well-known as a furniture MSME hub with products exported widely. However, challenges such as raw material cutting efficiency, production quality standardization, and limited working capital remain obstacles for business actors. The XYZ Regency Government is planning to develop a furniture industrial center to improve community welfare, increase global market competitiveness, and benefit various stakeholders. This study aims to evaluate the business feasibility of a furniture industrial center in XYZ from a financial perspective. The quantitative method used involved data collection through surveys and questionnaires engaging 1,155 furniture MSMEs in A and B Subdistricts. Analysis was conducted by calculating cost of goods manufactured (COGM), labor costs, overhead, and projected profit and loss. The results indicate that annual labor costs reach IDR 1,513,046,088, overhead is IDR 997,270,000, and non-production operational costs are IDR 724,560,000. The estimated Cost of Goods Sold (COGS) is IDR 3,234,876,088, with annual revenue potential of IDR 4,464,000,000 and a net profit of IDR 629,123,912. Projections show that the Break-Even Point (BEP) is expected to be achieved between the 8th and 9th years, with optimum operational targets being reached by the 10th year. This study provides a basis for XYZ Regency Government to make informed decisions regarding the development of the furniture industrial center business in the future.